ANALISIS TUNJANGAN PROFESI PADA KINERJA GURU ASN DI SMKN 1 AMPELGADING KABUPATEN MALANG - Biantoro, Wahyu Drajat (MAP (Jurnal Manajemen dan Administrasi Publik), 2024)
The performance of civil servants is becoming an increasingly strategic policy issue, because improving the performance of the apparatus has broad implications in political economic life. This type of research is descriptive research. In conducting descriptive qualitative research, when collecting data in general a researcher can find research data in the form of words, pictures, data here are interview transcripts, field data notes, personal documents, cameras, notes, and others. There is a relationship between professional allowances and improved work performance, in the workplace environment. Teacher performance directly affects student learning outcomes. Teachers who are able to design challenging and relevant lessons, and provide constructive feedback, can improve students' understanding and academic achievement. It is concluded that the implementation of the ASN teacher performance allowance system at SMKN 1 Ampelgading is an important step in the effort to improve the quality of education. However, the success of this system cannot be guaranteed by providing financial incentives alone. The analysis of teacher performance allowance needs to involve a holistic approach that includes various aspects of teacher performance and its impact on the learning process.